(untitled) - Stempleski, Susan (New York, 2007)
Talk Time is a three-level conversation course that provides speaking and listening practice based on everyday situations. Gentle progression of communicative activities in each lesson makes it ideal for less confident students. The Student CD, included at the back of the Student Book, contains recordings of the conversations to provide students with listening practice outside of the classroom.
Keywords: English language,English language; Grammar,Problems, exerises, etc